Relationship between gastroesophageal reflux and chronic kidney disease: A meta-analysis of 4 million patients - Chaponan-Lavalle, Andres (2025)
Background: Chronic kidney disease (CKD) has been associated with higher risk of gastrointestinal disorders, particularly Gastroesophageal reflux disease (GERD). However, the magnitude of this association and the underlying mechanisms remains unclear. Methods: A systematic search was conducted across major databases from inception to November 2024. We included cross-sectional and case-control studies evaluating the relationship between CKD and GERD. Data were extracted and analyzed using a random-effects model to calculate pooled odds ratios (ORs) and prevalence rates. Study quality was assessed using the Newcastle-Ottawa Scale, and heterogeneity was evaluated using the Cochran's Q test and I² statistic. Results: Nine studies involving 4,650,709 participants were included. The pooled prevalence of GERD among CKD patients was 18% (95% CI: 0.10-0.26, I² =93.64%). The pooled crude OR for the association between CKD and GERD was 2.53 (95% CI: 1.30-4.92) and adjusted OR was 1.48 (95% CI: 1.05-2.08). Conclusion: This meta-analysis reveals a marginally significant association between CKD and GERD, highlighting higher prevalence of GERD among individuals with CKD. Furthers studies are needed to elucidate the underlying pathophysiological mechanisms and potential clinical implications.